Surface Strain Redistribution on Structured Microfibers to Enhance Sensitivity of Fiber‐Shaped Stretchable Strain Sensors. Issue 5 (11th December 2017) - Liu, Zhiyuan; Qi, Dianpeng; Hu, Guoyu; Wang, Han; Jiang, Ying; Chen, Geng; Luo, Yifei; Loh, Xian Jun; Liedberg, Bo; Chen, Xiaodong
Abstract: Fiber‐shaped stretchable strain sensors with small testing areas can be directly woven into textiles. This paves the way for the design of integrated wearable devices capable of obtaining real‐time mechanical feedback for various applications. However, for a simple fiber that undergoes uniform strain distribution during deformation, it is still a big challenge to obtain high sensitivity. Herein, a new strategy, surface strain redistribution, is reported to significantly enhance the sensitivity of fiber‐shaped stretchable strain sensors. A new method of transient thermal curing is used to achieve the large‐scale fabrication of modified elastic microfibers with intrinsic microbeads. The proposed strategy is independent of the active materials utilized and can be universally applied for various active materials. The strategy used here will shift the vision of the sensitivity enhancement method from the active materials design to the mechanical design of the elastic substrate, and the proposed strategy can also be applied to nonfiber‐shaped stretchable strain sensors. Abstract : Surface strain redistribution in substrates significantly enhances sensitivity of fiber‐shaped stretchable strain sensors fabricated by thermal‐transient‐curing and Plateau–Rayleigh instability. Poly(dimethylsiloxane) (PDMS) microfibers with beads are produced in large scale. The beads regulate strain distribution. Novel sensors are well adhered to textiles for monitoring sports activities. This study opens up a new perspective of fiber‐shaped sensors and a method to enhance sensitivity.